1, 2-Bis(arylthio)arene synthesis via aryne intermediates. Issue 64 (22nd July 2019) - Mesgar, Milad; Nguyen-Le, Justin; Daugulis, Olafs
Abstract : Use of a bulky LDAM base allows for an efficient synthesis of 1, 2-bis(arylthio)arenes from aryl halides and triflates. Abstract : Lithium 1, 1-diadamantylamide (LDAM) base-promoted insertion of arynes into disulfide S–S bonds is described. After generation of arynes from readily available aryl halides and triflates, reactions with diaryl and diisopropyl disulfides afford the insertion products in moderate to excellent yields. Use of 1-cyclohexenyl triflate gave an excellent yield of 1, 2-bis(phenylthio)cyclohexene.